Unlocking the power of youth: harnessing technology to break through market barriers - Saskia de Klerk; Fiona Buick; Gayathri Ranasinghne (Journal of Innovation and Entrepreneurship)
Abstract Small and medium-sized enterprises (SMEs) are crucial to economic growth. To contribute effectively to economic growth, SMEs need adequate resources. Social media is an essential yet often underestimated resource for entrepreneurs, especially in developing countries. Social media has particularly created broader opportunities for younger entrepreneurs to engage in global markets. This research examines how youth entrepreneurs in Sri Lanka use social media to create and grow their ventures. Our findings reveal that social media significantly alters traditional enterprises’ creation and growth processes. Youth entrepreneurs in Sri Lanka use SM to identify and seize business opportunities. These platforms draw venture capital in resource-limited environments and enhance marketing by enabling the creation of engaging content that fosters brand loyalty. This research illustrates how entrepreneurs effectively leverage SM for strategic marketing, targeting specific market segments to generate excitement for new products and maintain a competitive edge. We explore how technology, particularly SM, could be a vital resource in developing contexts. Our findings highlight key skills and strategies, such as internationalization and innovative use of SM, that empower youth entrepreneurs to overcome challenges and succeed. This study provides valuable insights into the interaction between technology and entrepreneurship in emerging markets.